2021
DOI: 10.1108/ijchm-09-2020-0975
|View full text |Cite
|
Sign up to set email alerts
|

The influence of customer race on perceived discrimination, anger and coping strategies following subtle degradation of restaurant service

Abstract: Purpose The purpose of this study is to examine how customer race (Black vs White) influences the extent to which customers attribute an ambiguous service failure (i.e. subtle degradation of service) to discrimination and how perceived discrimination relates to customer anger and on-site coping behaviors (vindictive complaining, problem-solving complaining and avoidance). This study further investigated how customer race affects the strength of relationships among perceived discrimination, anger and these thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…( Adeinat, 2019 , Bakker et al, 2014 , Bufquin et al, 2017 , CDC, 2020 , Choi et al, 2016 , Guidry et al, 2019 , Guilford et al, 2017 , Hu, 2019 , Jang and Namkung, 2009 , Kapoor and Singhal, 2017 , Luo and Mattila, 2020 , Magnini and Zehrer, 2021 , Min and Joireman, 2021 , Namkung and Jang, 2007 , Namkung et al, 2011 , Park et al, 2020 , Schaller, 2006 , Schaller, 2011 , Stevens et al, 1995 , Tsai et al, 2009 )…”
Section: Uncited Referencesmentioning
confidence: 99%
“…( Adeinat, 2019 , Bakker et al, 2014 , Bufquin et al, 2017 , CDC, 2020 , Choi et al, 2016 , Guidry et al, 2019 , Guilford et al, 2017 , Hu, 2019 , Jang and Namkung, 2009 , Kapoor and Singhal, 2017 , Luo and Mattila, 2020 , Magnini and Zehrer, 2021 , Min and Joireman, 2021 , Namkung and Jang, 2007 , Namkung et al, 2011 , Park et al, 2020 , Schaller, 2006 , Schaller, 2011 , Stevens et al, 1995 , Tsai et al, 2009 )…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Previous studies suggested that customers’ attribution of blame to external sources (e.g. employees) arouses anger, which leads to negative customer response in the end (Byun and Jang, 2018; Min and Joireman, 2021). Although a great deal of attention has been paid to the importance of attribution of blame in-service failure literature, its relation to SST service failures remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although a great deal of attention has been paid to the importance of attribution of blame in-service failure literature, its relation to SST service failures remains largely unknown. Moreover, previous studies on the attribution of blame in the traditional service failure literature generally focused on situational factors (Byun and Jang, 2018; Min and Joireman, 2021) rather than customers’ individual factors. By showing the differences in customers’ tendency to blame SST based on subjective social class, this study provides evidence of subjective social class differences in attribution of SST during the process of service failure and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, behavioural guidelines should be implemented to minimize any misunderstanding of failed services and the likelihood of perceptions of discriminatory services (Min and Joireman, 2021). Many articles have shown evidence of customer discrimination towards service providers in both digital and traditional H&T services (Gold, 2019;Huang and Kwok, 2021).…”
Section: Hospitality and Tourism Servicesmentioning
confidence: 99%
“…This practical guideline informs and assists industrial practitioners in eliminating biases and reducing attributions of discrimination. The guideline follows the concept that "prevention is better that cure" (Min and Joireman, 2021). For example, selection techniques (e.g.…”
Section: Theoretical Contributionsmentioning
confidence: 99%